2018
DOI: 10.18203/2349-3291.ijcp20181445
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of specific learning disability and awareness among care providers in children between 8-12 years

Abstract: Background: Specific learning disability (SLD) is known to cause great amount of psychological stress to the children and their parents. Current study was aimed to find out the prevalence, profile of errors in Specific learning disability among school students studying in 3rd to 6th standard and their perception by teachers and parents.Methods: A Cross-sectional study was conducted at two Government and two Private Schools in Gwalior. 800 students studying 3rd to 6th standard. The details of every student were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Supportively P.Neeraja 2013; Prakash Petchimuthu, Neetu Sharma, Ajay Gaur, Ranjeet Kumar 2018; UrvashiGoel 2021; Ramesh Kumar Awasthi and Yash Pal Singh 2021; Deenu Chacko, KarunakaranVidhukumar 2020; R Rajesh, HoneymolSunney 2021; Abdul Gafoor, K 2015 revealed that mis-spelt words and missing letters were the most frequent reading and spelling errors, respectively. (3,17,18,19,20,21,22) Teachers effectively identified some kids as having specific reading issues. Still, the other 19 pupils had generalised ideas about their sub-par academic performance (P < 0,05).…”
Section: Discussionmentioning
confidence: 99%
“…Supportively P.Neeraja 2013; Prakash Petchimuthu, Neetu Sharma, Ajay Gaur, Ranjeet Kumar 2018; UrvashiGoel 2021; Ramesh Kumar Awasthi and Yash Pal Singh 2021; Deenu Chacko, KarunakaranVidhukumar 2020; R Rajesh, HoneymolSunney 2021; Abdul Gafoor, K 2015 revealed that mis-spelt words and missing letters were the most frequent reading and spelling errors, respectively. (3,17,18,19,20,21,22) Teachers effectively identified some kids as having specific reading issues. Still, the other 19 pupils had generalised ideas about their sub-par academic performance (P < 0,05).…”
Section: Discussionmentioning
confidence: 99%